Spread of Mycobacterium avium subsp. paratuberculosis through soil and grass on a mouflon (Ovis aries) pasture - Kaevska, Marija; Lvoncik, S; Lamka, J; Pavlik, I; Slana, I (Current microbiology, 2014)
The aims of this study were to describe spatial contamination of the environment on a mouflon pasture, as well as to assess the contamination of grass and roots after surface contamination and in depth contamination with feces and buried tissues from animals infected with Mycobacterium avium subsp. paratuberculosis (M. a. paratuberculosis). Samples of soil, roots, and aerial parts of plants were collected from different locations inside the mouflon pasture, and one control sample site was chosen outside the area where the animals are living. M. a. paratuberculosis DNA was present in all the examined sites and was more often detected in roots than in soil. DNA was detected at up to 80 cm of depth and was spatially more widespread than the initial hypothesis of M. a. paratuberculosis leaching vertically into deeper layers of soil. This study broadens our knowledge of the spread and persistence of M. a. paratuberculosis in an environment with highly infected animals.
Keywords: Soil; Mycobacterium avium subsp. paratuberculosis; paratuberkulóza; nemoci skotu; Animals; Cattle Diseases; Soil Microbiology; Poaceae; krmivo pro zvířata; lipnicovité; Paratuberculosis; zvířata; Cattle; Animal Feed; skot; půdní mikrobiologie; půda